2020
DOI: 10.1038/s41559-020-1225-3
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphosis shapes cranial diversity and rate of evolution in salamanders

Abstract: Metamorphosis is widespread across the animal kingdom and induces fundamental changes in the morphology, habitat, and resources used by an organism during its lifetime. Metamorphic species are likely to experience more dynamic selective pressures through ontogeny compared to those with single-phase life cycles, which may drive divergent evolutionary dynamics. Here, we reconstruct the cranial evolution of the salamander using geometric morphometric data from 148 species spanning their full phylogenetic, develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 80 publications
4
77
1
Order By: Relevance
“…2020; Fabre et al. 2020), suggesting that the genetic, developmental, and functional interactions of traits that shape phenotypic integration are replicated in patterns of trait evolution. As discussed above, many studies have suggested that evolutionary modularity promotes diversification of form.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2020; Fabre et al. 2020), suggesting that the genetic, developmental, and functional interactions of traits that shape phenotypic integration are replicated in patterns of trait evolution. As discussed above, many studies have suggested that evolutionary modularity promotes diversification of form.…”
Section: Discussionmentioning
confidence: 99%
“…2019b; Fabre et al. 2020). As such, we used the estimated within‐ and between‐module correlations ( ρ ) for the best‐supported model and grouped highly integrated regions into larger modules as previously described (Felice and Goswami 2018; Marshall et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most salamanders switch from a 'free-feeding' larval-to a post-metamorphic stage during ontogeny via metamorphosis [1][2][3]. A recent study suggests that in species undergoing metamorphosis, parts of the skull associated with feeding develop faster and more independently from the rest [4]. This in turn suggests that the form and function of skeletal elements associated with feeding may be more exible.…”
Section: Introductionmentioning
confidence: 99%